Analysis of Work Stress, Work Conflicts and Workload on Employee Performance in the General Section of the Medan Mayor's Office - Darmilisani, Darmilisani; Setiawan, Nashrudin; Ginting, Ice Lediana Br (Journal of Research in Social Science and Humanities, 2024)
This study aims to analyze the influence of work stress, work conflicts, and workload on employee performance in the General Section of the Medan Mayor's Office. The method used is an associative quantitative approach with the aim of testing the hypothesis that has been prepared. The population of this study consisted of all employees in the General Section of the Medan Mayor's Office, which amounted to 30 people, and the entire population was sampled. Primary data were collected through questionnaires measured using the Likert scale. The data collection method is carried out by observation and dissemination of questionnaires. The data obtained was analyzed using IBM SPSS 26 statistical software. The results of the study show that work stress, work conflict, and workload each have a significant effect on employee performance. In addition, simultaneously, work stress, work conflicts, and workload also have a significant effect on employee performance in the General Section of the Medan Mayor's Office.